A comparative analysis of PFAS in archive and fresh soil samples in England and implications for large-scale surveys - Beriro, D.J.; Bearcock, J.M.; Vane, C.H.; Marchant, B.; Martin, I.; Haslam, A.; Pickering, H.; Hughes, M.; James, A. (Environmental pollution (1987), 2025)
This research addresses a knowledge gap in the detectability, concentrations, and types of per and polyfluoroalkyl substances (PFAS) present in shallow soils in England, UK. While the water environment has been, and continues to be, the subject of significant testing and research for these chemicals, soils are still poorly understood. Estimates of anthropogenic background concentrations of PFAS helps with the assessment of potential contamination scenarios, setting benchmark levels and risk evaluation. This research comprised an assessment of the suitability of using archive soil samples to support contemporary samples to give a preliminary indication of likely anthropogenic background concentrations of PFAS in shallow soils in England. We retrieved 25 archive samples and collected nine contemporary samples from the same geographical location as their paired archive counterpart. Samples were analysed for 53 PFAS with limits of quantification between 0.1 and 0.5 μg/kg dry weight (dw). The results showed that archive samples contained lower concentrations (mean ∑PFAS-53, 1 μg/kg dw) than paired contemporary soil samples (mean ∑PFAS-53, 3 μg/kg dw). The concentrations reported by this study were similar to other surveys at international, national and regional scales. Our study showed that PFAS were detected in both archive and contemporary field samples. Based on the current availability of archive samples in England, contemporary field samples should be used as the primary sample type in future research on background concentrations of PFAS in soils. Archive samples have the potential provide complimentary temporal and compositional insights to support the derivation of background concentrations. [Display omitted] •Soil concentrations of PFAS were measured in - background archive and field samples.•Eleven PFAS were detected in archived shallow soil samples (mean, 1 μg/kg dw).•Nine PFAS were detected in fresh shallow soil samples (mean, 3 μg/kg dw).•Large scale background PFAS surveys should be primarily based on present-day samples.•Archive samples could play a supporting role in estimating background PFAS in soil.